PENGARUH SOSIALISASI PERPAJAKAN, PELAYANAN APARAT PAJAK DAN PEMAHAMAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DENGAN PREFERENSI RISIKO SEBAGAI VARIABEL MODERASI - Heliani (Jurnal Aktiva : Riset Akuntansi dan Keuangan, 2019)
This research aims to examine :the influence of socialization of taxation, service tax officers, understanding of taxpayer, and risk preferences on tax compliance, this research also aims to examine the moderating influence of risk preferences for the relationship between socialization of taxation with taxpayer’s compliance, this research also aims to examine the moderating influence of risk preference for the relationship between service tax officer with taxpayer’s compliance, this research also aims to examine the moderating influence of risk preference for the relationship between understanding of taxpayer with taxpayer’s compliance. The sampling method of this research used convenience sampling with a sample of 155 respondent from individual taxpayer’s at the Sukabumi tax office. The research data used are the primary data by questionnaire which have contained respondent answer’s. In this research, data analysis used by Moderated Regression Analysis. The results showed that the socialization of taxation, service tax officers, understanding of taxpayer and risk preferences have a positive effect on taxpayer compliance. Besides the moderating variable that risk preferences is not strengthen the positive influence on the relationship between socialization of taxation, service tax officer and understanding of taxpayer with taxpayer’s compliance.